Understanding an Option to Renew a Lease: AREIF (Singapore I) Pte Ltdv NTUC Fairprice Co-operative Ltd [2015] SGHC 28 - SEE, Alvin W. L. (Institutional Knowledge at Singapore Management University, 2015)
The dispute in this case arose from the attempt by NTUC Fairprice Co-operative Ltd (“NTUC”), operator of the well-known chain of Fairprice supermarkets, to renew a lease of seven units (“the premises”) in a commercial building located close to the busy Orchard shopping district. The landlord, AREIF (Singapore I) Pte Ltd (“AREIF”), refused renewal and eventually leased the premises to a competing supermarket chain, Cold Storage. Before the High Court, the legal issue to be decided was whether, on the proper construction of the relevant term of lease agreement, AREIF was under any obligation to renew the lease.